The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1177/193229680900300109
|View full text |Cite
|
Sign up to set email alerts
|

Self-Monitoring of Blood Glucose in Type 1 Diabetes Patients with Insufficient Metabolic Control: Focused Self-Monitoring of Blood Glucose Intervention Can Lower Glycated Hemoglobin A1C

Abstract: Little attention has been given and few studies have been published focusing on how to optimize self-monitoring of blood glucose (SMBG) use to monitor daily therapy for persons with type 1 diabetes mellitus. This study was designed to evaluate the effect on glycated hemoglobin (A1C) of a structured intervention focused on SMBG in type 1 diabetes patients with insufficient metabolic control (A1C ≥ 8%) using a randomized clinical trial design. Method:One hundred fifty-nine outpatients with type 1 diabetes on mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 22 publications
5
23
2
2
Order By: Relevance
“…The magnitude of the benefit was small, with (absolute) A1C reductions in these meta-analyses ranging from 0.2% to 0.5%. These analyses demonstrated greater A1C reductions in those performing SMBG when the baseline A1C was >8% (17,35,38,42). SMBG has been demonstrated to be most effective in persons with type 2 diabetes within the first 6 months after diagnosis (43).…”
Section: Type 2 Diabetes Not Treated With Insulinmentioning
confidence: 90%
“…The magnitude of the benefit was small, with (absolute) A1C reductions in these meta-analyses ranging from 0.2% to 0.5%. These analyses demonstrated greater A1C reductions in those performing SMBG when the baseline A1C was >8% (17,35,38,42). SMBG has been demonstrated to be most effective in persons with type 2 diabetes within the first 6 months after diagnosis (43).…”
Section: Type 2 Diabetes Not Treated With Insulinmentioning
confidence: 90%
“…[28][29][30][31] Evidence also suggests that more structured, focused SMBG intervention in suboptimally controlled patients with type 1 diabetes can provide significant improvements in HbA1c compared with regular guideline-based care. 32 Like in type 1 diabetes, the rationale for the use of SMBG in insulin-treated type 2 diabetes is compelling and is supported by data from large prospective and observational trials. 30,33,34 Similar to the Diabetes Control and Complications Trial, the Kumamoto study showed that intensive insulin therapy guided by SMBG can reduce the risk of microvascular complications compared with conventional therapy in type 2 diabetes.…”
Section: What Do the Guidelines Say On Smbg In Diabetes?mentioning
confidence: 99%
“…', Skeie et al [41] designed the 'MEASURE' (Metabolic Effects of Accurate Blood Sugar Results and Education in Type 1 Diabetes) trial. They evaluated the effect of a simple, structured, realistic SMBG intervention on the metabolic Normal daily life At least prior to meals and snacks, occasionally postprandially, at bedtime [27] Person injecting 1-2 times/day At least 2 times a day [37] Person who alters insulin doses at mealtimes At least 4 times a day [37] Hypoglycemia To confirm hypoglycemia, every 15 min after treating low blood glucose until the euglycemia [27] Driving Before driving and at 2-hour intervals during long journeys [37] Before driving and at regular intervals for journeys of 1 h or longer in drivers who are at risk for developing hypoglycemia [52] Intercurrent control in patients with T1DM and long-standing experience in performing SMBG.…”
Section: Starting/changing Therapymentioning
confidence: 99%